2018
DOI: 10.11113/lspi.v5n2.81
|View full text |Cite
|
Sign up to set email alerts
|

Use of Action Songs and Total Physical Response to Promote the Development of Listening Skills among Year 4, Low Enrolment-Tamil Vernacular Primary School Students in Malaysia

Abstract: Total Physical Response (TPR) is built around the coordination of speech and actions. Action songs promote dance or acts while singing. In this study, we look at action songs as part of TPR to investigate its effectiveness in enhancing students’ listening skills to develop their mastery of the English Language. Seven Year 4 students from a Low Enrolment (SKM) Tamil Vernacular Primary school type (SJKT) were selected as the participants of a within-group experimental design. Upon completing a pre-test on listen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Movies and music (providing audio- and visual authentic input) were also considered as a source of enhancing other language skills such as listening, speaking, grammar and pronunciation (reported in the mastery orientation category of playfulness in the results section). This is in line with different studies that also confirmed the effective role of movies and music in enhancing listening skill (e.g., Qiu and Huang, 2012 ; Kumar and Sandaran, 2018 ) and speaking acquisition (e.g., Porcel, 2010 ), grammar (e.g., Mushtaq and Zehra, 2016 ) and pronunciation mastery.…”
Section: Discussionsupporting
confidence: 91%
“…Movies and music (providing audio- and visual authentic input) were also considered as a source of enhancing other language skills such as listening, speaking, grammar and pronunciation (reported in the mastery orientation category of playfulness in the results section). This is in line with different studies that also confirmed the effective role of movies and music in enhancing listening skill (e.g., Qiu and Huang, 2012 ; Kumar and Sandaran, 2018 ) and speaking acquisition (e.g., Porcel, 2010 ), grammar (e.g., Mushtaq and Zehra, 2016 ) and pronunciation mastery.…”
Section: Discussionsupporting
confidence: 91%
“…Utilising songs in the language classrooms can motivate passive pupils to become active listeners and participants thus improving their lack of motivation to learn English. This is echoed by Kumar and Sandaran (2018) who identified the potential of employing songs in language classrooms that makes learning fun and meaningful, especially in teaching listening skills. Furthermore, studies have showcased that music enables primary pupils to gain positive impacts, thus reiterating its advantageous point in enhancing literacy development (e.g.…”
Section: Literature Review Second Language Acquisitionmentioning
confidence: 99%
“…Since Malay is the main medium of instruction in National Schools, English is taught as a second language. As for the vernacular schools where mother tongue such as Mandarin or Tamil is the medium of instruction, Malay is taught as a second language whereas English is taught as a third language (Kumaran & Krish, 2021;Kumar & Sandaran, 2018). Learning English as a third language is one of the reasons for vernacular school students' poor English language proficiency and they perceive it as a difficult subject (Maniam, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Students from Tamil vernacular schools thus, have less exposure to the English language which may hinder their acquisition of the English language. As stated by Kumar & Sandaran (2018), using the first language which is Tamil is prohibited among teachers and students during English lessons, and students struggle to understand the teachers' instructions, which are solely in English language. Since code-switching is not allowed in the classroom, some students have apprehensions about learning the English Language (Kumar & Sandaran, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation